(untitled) (Journal of Advanced Research in Social Sciences, 2023)
The political stability of a government depends on the norms that come from a state of rights. Several metrics have been proposed to measure political stability, but they must be applied carefully to individual countries or to compare countries. In the related literature the cultural factors are not directly considered and are limited to quantifying their practical effects. Concepts such as contempt for authority have not been directly quantified. This study proposes indicators that account for the cultural concept of contempt for authority and permit a rapid quantitative and visual analysis of the political stability of a country or province throughout its history. A specific historical analysis for the Republic of Argentina between the 16th and 21st centuries was realized. The results found indicate 1) the permanence of socially toxic behavior patterns in Argentina and other Latin American countries, 2) that inherited cultural causes could explain the high political instability in Argentina over the last 500 years and 3) a succession of singles term length by ruler during decades could be used to stabilize a country.